2021
DOI: 10.3390/app11146294
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chitosan-Genipin Films on Volatile Profile of Wine along Storage

Abstract: Chitosan-genipin films have been proposed for preservation of white wine, maintaining their varietal key odorants and organoleptic characteristics of sulfur dioxide treated wines. Nevertheless, these wines showed aroma notes that slightly distinguish them. It is possible that during the contact of films with wine for at least 2 months, after fermentation and prior to bottling, interactions or chemical reactions are promoted. In this work, wine model solutions with volatile compounds in contact with chitosan-ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…The DVB/CAR/PDMS coating contains both adsorbents that are layered to extend the molecular weight range of analytes extracted with one SPME fiber and the combination with the PDMS, an absorptive-type fiber that also confers a bipolar character (Shirey, 2012; Godage and Gionfriddo, 2019; Carriço et al, 2020). This arrangement explains the high performance of the DVB/CAR/PDMS fiber for a wide range of chemical species and the fact that it is extensively used for profiling of volatile molecules released from various food items, such as table and fortified wine (Perestrelo et al, 2011;Santos et al, 2013;Welke et al, 2014;Whitener et al, 2016;Rocha et al, 2021), beer (Sterckx et al, 2010;Rodriguez-Bencomo et al, 2012;Romero-Medina et al, 2020), sea salt (Donadio et al, 2011;Silva et al, 2015), pear (Wang et al, 2019;Fonseca et al, 2020), distilled beverages (Thibaud et al, 2020), coffee (Ongo et al, 2020;Lopes et al, 2021), elderberry (Salvador et al, 2016), hazelnut (Cordero et al, 2010;Rosso et al, 2020), honey (Čajka et al, 2007;Siegmund et al, 2018), dairy products (Cardinali et al, 2021;Székelyhidi et al, 2021;Liu et al, 2022), virgin olive oil (Purcaro et al, 2014;Ros et al, 2019), and cereals (Buśko et al, 2010). Indeed, DVB/CAR/PDMS fiber exhibited the highest sorption capacity for a wide range of VOCs released from honey, comparing with six other fiber coatings (Čajka et al, 2007).…”
Section: Solid-phase Microextractionmentioning
confidence: 99%
See 2 more Smart Citations
“…The DVB/CAR/PDMS coating contains both adsorbents that are layered to extend the molecular weight range of analytes extracted with one SPME fiber and the combination with the PDMS, an absorptive-type fiber that also confers a bipolar character (Shirey, 2012; Godage and Gionfriddo, 2019; Carriço et al, 2020). This arrangement explains the high performance of the DVB/CAR/PDMS fiber for a wide range of chemical species and the fact that it is extensively used for profiling of volatile molecules released from various food items, such as table and fortified wine (Perestrelo et al, 2011;Santos et al, 2013;Welke et al, 2014;Whitener et al, 2016;Rocha et al, 2021), beer (Sterckx et al, 2010;Rodriguez-Bencomo et al, 2012;Romero-Medina et al, 2020), sea salt (Donadio et al, 2011;Silva et al, 2015), pear (Wang et al, 2019;Fonseca et al, 2020), distilled beverages (Thibaud et al, 2020), coffee (Ongo et al, 2020;Lopes et al, 2021), elderberry (Salvador et al, 2016), hazelnut (Cordero et al, 2010;Rosso et al, 2020), honey (Čajka et al, 2007;Siegmund et al, 2018), dairy products (Cardinali et al, 2021;Székelyhidi et al, 2021;Liu et al, 2022), virgin olive oil (Purcaro et al, 2014;Ros et al, 2019), and cereals (Buśko et al, 2010). Indeed, DVB/CAR/PDMS fiber exhibited the highest sorption capacity for a wide range of VOCs released from honey, comparing with six other fiber coatings (Čajka et al, 2007).…”
Section: Solid-phase Microextractionmentioning
confidence: 99%
“…Also, to avoid cross-over contaminations, thermal clean-ups between extractions have to be done. All the previously reported advantages are the justification for the fact that SPME has been successfully used as an extraction technique for a wide range of foodstuffs and beverages ( Kataoka et al, 2000 ; Peñalver et al, 2000 ; Vesely et al, 2003 ; Vichi et al, 2003 ; Pawliszyn, 2009 ; Giri et al, 2010 ; Welke et al, 2014 ; Alves et al, 2015 ; Santos et al, 2015 ; Silva et al, 2015 ; Nunes et al, 2016 ; Salvador et al, 2016 ; Xu et al, 2016 ; Martins et al, 2018 , 2020 ; Fonseca et al, 2020 ; Bressanello et al, 2021 ; Lopes et al, 2021 ; Rocha et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In oenology, the use of chitosan has been authorized by the International Organization of Vine and Wine (OIV) for wine clarification and treatment (as it helps reduce heavy metal contents and other contaminants). In this context, chitosan obtained from the Aspergillus niger fungus is commonly used, in concentrations not exceeding 1 g/L [ 7 , 8 ]. However, chitosan films obtained from shrimp by-products have also been advanced as a potentially more easily obtainable alternative material, with similar mechanical and chemical properties (and the absence of allergenicity) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reticulation of chitosan with genipin (the aglycone derivative of geniposide, a bioactive glycoside found in Gardenia fruits) can be used to produce cross-linked films (Ch-Ge films) with improved stability in acidic aqueous matrices (such as wines, pH close to 3.5). These reticulated films show suitable mechanical properties and favorable antioxidant and antimicrobial characteristics, thus having been proposed for white wine preservation strategies [ 7 , 9 ]. The organoleptic assessment of white wines treated with Ch-Ge films (with an area of 100 cm 2 ) compared to the traditional SO 2 method revealed that the expected characteristic varietal notes of wines were maintained [ 7 , 9 ], while microbial growth was inhibited, as no yeast or bacterial growth were detected over a 12-month storage period [ 9 ].…”
Section: Introductionmentioning
confidence: 99%